Christian missions and humanitarianism in the Middle East, 1850-1950: ideologies, rhetoric, and practices - Okkenhaug, Inger Marie; Sanchez-Summerer, Karene (Leiden studies in Islam and society, 2020)
"From the early phases of modern missions, Christian missionaries supported many humanitarian activities, mostly framed as subservient to the preaching of Christianity. This anthology contributes to a historically grounded understanding of the complex relationship between Christian missions and the roots of humanitarianism and its contemporary uses in a Middle Eastern context. Contributions focus on ideologies, rhetoric, and practices of missionaries and their apostolates towards humanitarianism, from the mid-19th century Middle East crises, examining different missionaries, their society's worldview and their network in various areas of the Middle East. In the early 20th century Christian missions increasingly paid more attention to organisation and bureaucratisation ('rationalisation'), and media became more important to their work. The volume analyses how non-missionaries took over, to a certain extent, the aims and organisations of the missionaries as to humanitarianism. It seeks to discover and retrace such 'entangled histories' for the first time in an integral perspective. Contributors include: Beth Baron, Philippe Bourmaud, Seija Jalagin, Nazan Maksudyan, Michael Marten, Heleen (L.) Murre-van den Berg, Inger Marie Okkenhaug, Idir Ouahes, Maria Chiara Rioli, Karène Sanchez Summerer, Bertrand Taithe, and Chantal Verdeil"--